Ultrasound-assisted extraction of collagen from broiler chicken trachea and its biochemical characterization - Kitsanapong Kaewbangkerd; Ali Hamzeh; Jirawat Yongsawatdigul (Ultrasonics Sonochemistry, 2023)
Broiler chicken tracheas are a co-product from chicken slaughterhouses which are normally turned into low value animal feed despite their high levels of collagen. Typical collagen extraction by acid and/or pepsin usually results in relatively low yield. Ultrasound-assisted extraction (UAE) could be a means to improve collagen yield. The objectives of this study were to investigate the effects of ultrasonic parameters on the yield and biochemical properties of trachea collagen (TC). Conventional extraction using acetic acid and pepsin for 48 h resulted in acid-soluble (AS) and pepsin-soluble (PS) collagen with a yield of 0.65% and 3.10%, respectively. When an ultrasound with an intensity of 17.46 W·cm−2 was applied for 20 min, followed by acid extraction for 42 h (U-AS), the collagen yield increased to 1.58%. A yield of 6.28% was obtained when the ultrasound treatment was followed by pepsin for 36 h (U-PS). PS and U-PS contained collagen of 82.84% and 85.70%, respectively. Scanning electron microscopy images revealed that the ultrasound did not affect the collagen microstructure. All collagen samples showed an obvious triple helix structure as measured by circular dichroism spectroscopy. Fourier transform infrared spectroscopy indicated that the ultrasound did not disturb the secondary structure of the protein in which approximately 30% of the α-helix content was a major structure for all collagen samples. Micro-differential scanning calorimetry demonstrated that the denaturation temperature of collagen in the presence of deionized water was higher than collagen solubilized in 0.5 M acetic acid, regardless of the extraction method. All collagen comprised of α1 and α2-units with molecular weights of approximately 135 and 116 kDa, respectively, corresponding to the type I characteristic. PS and U-PS collagen possessed higher imino acids than their AS and U-AS counterparts. Based on LC-MS/MS peptide mapping, PS and U-PS collagen showed a high similarity to type I collagen. These results suggest that chicken tracheas are an alternative source of type I collagen. UAE is a promising technique that could increase collagen yield without damaging its structure.